La Conciencia Léxica en el Desarrollo de la Lecto-Escritura En Los Niños Y Niñas de Segundo Grado Básico De La Unidad Educativa “Chile” Parroquia Punin Cantón Riobamba, Provincia de Chimborazo Periodo Lectivo 2014-2015” - Andrade Pilamunga, Martha Liliana (2017)
In this educational proposal a diagnosis was made of the problems that the students show at the moment of the consolidation of the lexical conscience, as a point of reference I have proposed innovative activities that are of interest for the students and that help the teacher in the moment of teaching phonological awareness; I have set forth feasible objectives that will help the student acquire this lexical awareness skill and complement the work of the other sciences, such as: semantics, lexical, pragmatic and syntactic, in this way students acquire the ability to identify phonemes and its graphic representation in the first years of education that is fundamental to reach the literacy. For this work we used the inductive, deductive and hermeneutical methods according to the types of research is descriptive, correlational and explanatory, therefore I have managed to identify the problem raised, and the importance of lexical awareness in the development of reading and writing in the boys and girls of the second grade in a basic educational institution called "Chile" throughout the educational process and generalize the results, the technique that was used is observation and as an instrument the observation sheet that was structured with ten items related to the both variables. It has been possible to reach an optimum development of oral language, both comprehensively and expressively, and to enhance the work of linguistic and metalinguistic abilities, which are one of the fundamental pillars in the access to reading and writing.